Gauging the Effectiveness of Six-week Internship Duration in Business Education in Pakistan: Implications for Policy and Practice - Nasreen Hussain (Journal of Education and Educational Development, 2020)
This small scale research was conducted to understand whether the duration of six-week internship which has been set by Higher Education Commission Pakistan is enough for interns to fulfill their desired objectives or not. To understand the issue at hand, semi-structured interviews were conducted with 22 interns who had completed their internship, regarding their views on time period of six-weeks. It was revealed that even though the majority of the interns thought that a six-week time period was not enough for them to achieve their learning objectives, the review of the literature and intern interviews discovered that the internships were not designed effectively and therefore could not deliver the desired results in the specified time.
Keywords: interns; internships; higher education commission; Pakistan